Waiting for the Magic - MacLachlan, Patricia; Bates, Amy June (New York : Atheneum Books for Young Readers, 2011)
When Papa goes away for a little while, his family tries to cope with the separation by adopting four dogs and a cat.
Ages 8-12.
Keywords: Separation anxiety in children -- Fiction; Family life -- Fiction; Dogs -- Fiction; Cats -- Fiction; Human-animal relationships -- Fiction